An Antlion, Glenurus gratus (Say) (Insecta: Neuroptera: Myrmeleontidae) - Robert B. Miller; Lionel A. Stange (EDIS)
EENY-393, a 4-page illustrated fact sheet by Robert B. Miller and Lionel A. Stange, describe these common, conspicuous insects in Florida, also known as "doodlebugs." Includes sections on distribution, identification, biology, detection and survey, economic importance, and selected references. Published by the UF Department of Entomology and Nematology, October 2006.